PENDIDIKAN AGAMA ISLAM DALAM PERSPEKTIF FILSAFAT: ANTARA CITA DAN FAKTA - Majid, Mohamad Arif (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2015)
Islamic education is a long life process in digging and performing Islamic values of (raḥmatan li al-’alamīn). It is also long-life attempts to excavate raḥmatan values amid the challenges of modernity and thoughts. This article discusses Islamic education from a philosophical perspective. This study found that ontologically theessence of Islamic education is on the process, while epestemoligically it requires the interaction between ratio and revelation. Axiologically, Islamic education should bring dignity, prominence, and happiness both in the word and the hereafter. This is what the so-called a ‘two in one’ concept and the key is ‘lillāh.Keywords: Pendidikan Agama Islam, Filsafat, Raḥmatan li al-’Alamīn